Ephrin Receptors (Ephs) Expression in Thymic Epithelial Tumors: Prognostic Implications and Future Therapeutic Approaches - Christos Masaoutis; Natalia Georgantzoglou; Panagiotis Sarantis; Irene Theochari; Nikolaos Tsoukalas; Mattheos Bobos; Paraskevi Alexandrou; Alexandros Pergaris; Dimitra Rontogianni; Stamatios Theocharis (Diagnostics, 2021)
Ephrin receptors (Ephs) are receptor tyrosine kinases (RTKs) implicated in tissue development and homeostasis, and they are aberrantly expressed in tumors. Here, immunohistochemical Eph type-A and -B expression in thymic epithelial tumors (TETs) was assessed and correlated with clinicopathological parameters. Tissue microarrays from 98 TETs were stained for EphA1, -A2, -A4 -A6, -B1, -B2, -B4 and -B6. The relationship between neoplastic and lymphoid cell immunoreactivity score (H-score), histopathological parameters (Pearson’s test) and survival of 35 patients (Mantel-Cox model) was explored. Epithelial-rich subtypes showed higher EphA6 cytoplasmic H-score (B2/B3, carcinoma) (p < 0.001) and stronger EphA4 H-score (B3, carcinoma) (p = 0.011). The immature T-cells, especially in subtypes AB/B1, had higher EphB6 H-score than carcinoma-associated mature lymphocytes (p < 0.001); carcinomas had higher lymphocytic EphB1 H-score (p = 0.026). Higher lymphocytic and lower epithelial EphB6 H-score correlated with Masaoka stage ≤II (p = 0.043, p = 0.010, respectively). All cases showed variable epithelial and lymphocytic EphA2 expression, but clinicopathological associations were not reached. Our study confirmed that Eph type-A and -B expression in TETs is associated with established prognostic parameters, i.e., tumor subtype and Masaoka stage, although correlation with patient survival was not reached. Such findings suggest involvement of these RTKs in thymic neoplasia, as well as their potential utility as treatment targets.